Particle Size Effect in Model Retaining Wall on Passive Mode with Granular Material - . Erizal; Toshinori Sakai (PERTETA, 2000)
This paper presented a particle size effect on model retaining wall by comparing the experimental and finite element analysis. The experiments were conducted with air-dried Toyoura sand and Soma sand plane strain condition, both sand are standard sand in Japan. The wall was oved horizontally into sand. The hights of sand mass in these experiments were 5 cm, 10 cm, and 15 cm. The finite element analysis employed a constitutive model in which non-associated strain hardening-softening elasto-plastic materila was employed. This analysis introducted the effect of shear band thickness. The result obtained from the finite element analysis showed a good agrement with the results obtained from the experimental investigation. From both experimental and analytical results, there was evident of particle size effect due to shear banding.